Kinetics and Mechanism of Periodate Oxidation of m-Toluidine in Acetone-Water Medium - Kaushik*, R.D.; Joshi, Rajesh (Asian Journal of Chemistry, 2010)
Calcium complexes of malonic, succinic and glutaric acids have been investigated by conductometric titrations. The data indicated the formation of binary 1:1 and 1:2 calcium malonate, 1:1, 1:2 and 1:3 calcium succinate and glutarate complexes.